Individual with Visual Impairment and Translation: A Case Study of Visually Impaired Translator in Translating News Text of TVKU - Valentina Widya Suryaningtyas; Setyo Prasiyanto Cahyono (Lecturer Association of Linguistics, Language Teaching, and Literature Studies in Indonesi, 2018)
This article is of specialized translation study. It discusses a translation activity conducted by a visually impaired translator. The study focuses on the translation techniques, methods, and ideology which are carried out by the translator. Using qualitative descriptive method, the authors are able to identify that the translator uses five translation techniques. Four (addition, reduction, adaptation, and generalization) are target-language-oriented techniques and one technique is source-language-oriented one (borrowing). In translating TVKU news text, the subject of the study applies four translation steps. To conclude, the translator’s cognitive concept affects his decision to translate the text.